1999
DOI: 10.1557/proc-585-103
|View full text |Cite
|
Sign up to set email alerts
|

Thin Film Growth and Ion-Beam Modification: Md Simulations Going Beyond Simple Systems

Abstract: Molecular Dynamics computer simulations were used to explore a number of complex phenomena that occur during film growth and ion-surface interactions. A few examples are discussed. (1) Strong surface patterns develop when a Mo film is grown on a Mo(110) substrate, whereas they are absent for Mo on Mo(100). (2) Depositing a Mo film on a substrate containing two antiparallel (100)/(910) grain boundaries leads to complicated film morphologies in the grain boundary regions. Stresses, mosaic spread, and regions of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Additional evidence for this is found in results from molecular-dynamics simulation of Cu growth on Mo͑110͒. 22,23 Now we return to discussing the individual spectra in Fig. 3.…”
Section: B Effect Of Film Thicknessmentioning
confidence: 71%
“…Additional evidence for this is found in results from molecular-dynamics simulation of Cu growth on Mo͑110͒. 22,23 Now we return to discussing the individual spectra in Fig. 3.…”
Section: B Effect Of Film Thicknessmentioning
confidence: 71%
“…Haddeman et al reported an activation energy of 10.6 kJ/mole for Ion Beam Assisted Deposition (IBAD)-Mo film as a barrier layer using the Arrhenius plot. 28 Our prior studies show that the copper-silicide formation temperature of Cu-W films is higher than the Cu-Mo film. 24 Moreover, the activation energy for copper-silicide formation is slightly higher than the Cu-Mo film.…”
Section: Thermal Analysismentioning
confidence: 95%